Enhancing longitudinal studies by linkage to national databases: "Growing Up in Australia", The Longitudinal Study of Australian Children - Harrison, L; Sanson, A; Wake, M; Soloff, C; Ungerer, J (My University, 2006)
'Growing Up in Australia' is a national longitudinal study of the development and wellbeing of 10,000 Australian children. It collects information on children?s mental and physical health, social adjustment, cognitive development and school achievement, experiences at home, in child care, at school and in the community and relevant data such as socioeconomic information. It supports data linkage to other datasets, which adds value to the central approaches to data collection from parents and others. Potential data sources need to be evaluated by considering: the relevance of the data for research questions, policy and/or scientific advances; the quality of the data; the impact on participant recruitment and retention; respondent and interviewer burden; procedures required for informed consent; protection of privacy; cost, in terms of both time required (or saved), and financial cost; when and how often the data can be collected/linked; and the ease of obtaining the data. This article documents the various sources for data linkage considered for Growing Up in Australia, including government health and education records, child care accreditation data, and community-level data, and examines the strengths and challenges associated with each.
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology